Investigation of physical and chemical properties of new derivatives of 5-(thiophene-3-ylmethyl)-4R-1,2,4-triazole-3-thiols - Khilkovets, A. V.; Хільковець, Анастасія Валеріївна; Хильковец, А. В. (Запорізький державний медичний університет, 2021)
Heterocyclic compounds are one of the most important branches of modern organic chemistry and are widely used in medicine, pharmacy, agriculture, and in the production of new materials. One of these compounds is 1,2,4-triazole, which has attracted the attention of scientists around the world for many years. The aim of the work is to synthesize new derivatives of 5-(thiophene-3-ylmethyl)-4R-1,2,4-triazole-3-thiols and study their physicalchemical properties, conducting primary pharmacological screening. Materials and methods. Organic synthesis classical methods were used in the study, as well as a complex of physical-chemical analysis methods (1H NMR spectroscopy, elemental analysis, Elisa and chromato-mass spectral studies) were done. Prediction of pharmacological activity was carried out by using the PASS online computer program. Results. Two initial compounds were obtained: 5-(thiophene-3-ylmethyl)-4phenyl-1,2,4-triazole-3-thiol and 5-(thiophene-3-ylmethyl)-4H- 1,2,4-triazole-3-thiol. During their further chemical transformation, a number of new corresponding alkyl derivatives were obtained. The structure of the synthesized compounds was confirmed using modern physical-chemical methods of analysis. Based on the results of pharmacological screening, the high activity of the obtained compounds can be predicted. Conclusions. 5-(thiophene-3-ylmethyl)-4H-1,2,4-triazole-3-thiol, 5-(thiophene-3-ylmethyl)-4-phenyl-1,2,4-triazole-3-thiol and a number of their alkyl derivatives were synthesized. The structure and individuality were proved thanks to modern physical and chemical methods of analysis. Having analyzed the results of primary pharmacological screening of a number of obtained compounds, some of them were selected for further study. Гетероциклічні сполуки – один із найважливіших розділів сучасної органічної хімії, що широко застосовуються в медицині, фармації, сільському господарстві та під час отримання нових матеріалів. Одна з таких сполук – 1,2,4-тріазол, який протягом багатьох років привертає увагу науковців усього світу. Мета роботи – синтез нових похідних 5-(тіофен-3-ілметил)-4R-1,2,4-тріазол-3-тіолів і дослідження їхніх фізико-хімічних властивостей, здійснення первинного фармакологічного скринінгу. Матеріали та методи. Під час дослідження використали класичні методики органічного синтезу, а також застосували комплекс фізико-хімічних методів аналізу (1Н ЯМР спектроскопія, елементний аналіз, ІЧ та хромато-мас-спектральні дослідження). Прогнозування фармакологічної активності здійснили за допомогою комп’ютерної програми PASS online. Результати. Отримали дві вихідні сполуки: 5-(тіофен-3-ілметил)-4феніл-1,2,4-тріазол-3-тіол і 5-(тіофен-3-ілметил)-4Н-1,2,4- тріазол-3-тіол. Під час наступних хімічних перетворень одержали ряд нових відповідних алкілпохідних. Структура синтезованих сполук підтверджена з використанням сучасних фізико-хімічних методів аналізу. За результатами фармакологічного скринінгу можна прогнозувати високу активність нових сполук. Висновки. Синтезували 5-(тіофен-3-ілметил)-4Н-1,2,4-тріазол-3-тіол, 5-(тіофен-3-ілметил)-4-феніл-1,2,4-тріазол-3-тіол і ряд їхніх алкілпохідних. Будову та індивідуальність сполук довели з застосуванням сучасних фізико-хімічних методів аналізу. Проаналізувавши результати первинного фармакологічного скринінгу, деякі з ряду сполук обрали для наступних досліджень. Гетероциклические соединения – один из важнейших разделов современной органической химии, широко применяются в медицине, фармации, сельском хозяйстве и при получении новых материалов. Одно из таких соединений – 1,2,4-триазол, который в течение долгих лет привлекает внимание учёных всего мира. Цель работы – синтез новых производных 5-(тиофен-3-илметил)-4R-1,2,4-триазол-3-тиолов и исследование их физико-химических свойств, проведение первичного фармакологического скрининга. Материалы и методы. В ходе исследования применяли методы классического органического синтеза, а также использован комплекс физико-химических методов анализа (1Н ЯМР спектроскопия, элементный анализ, ИК и хромато-масс-спектральные исследования). Прогнозирование фармакологической активности проведено с помощью компьютерной программы PASS online. Результаты. Получены два исходных соединения: 5-(тиофен-3-илметил)-4фенил-1,2,4-триазол-3-тиол и 5-(тиофен-3-илметил)-4Н-1,2,4-триазол-3-тиол. В ходе дальнейших химических преобразований получен ряд новых соответствующих алкилпроизводных. Структура полученных соединений подтверждена современными физико-химическими методами анализа. По результатам фармакологического скрининга можно спрогнозировать высокую активность полученных соединений. Выводы. Синтезировали 5-(тиофен-3-илметил)-4Н-1,2,4-триазол-3-тиол, 5-(тиофен-3-илметил)-4-фенил-1,2,4-триазол-3-тиол и ряд их алкилпроизводных. Строение и индивидуальность доказаны с использованием современных физико-химических методов анализа. Проанализировав результаты первичного фармакологического скрининга, некоторые соединения из полученного ряда отобрали для дальнейших исследований.
Дослідження фізико-хімічних властивостей нових похідних 5-(тіофен-3-ілметил)-4R-1,2,4-тріазол-3-тіолів
Исследование физико-химических свойств новых производных 5-(тиофен-3-илметил)-4R-1,2,4-триазол-3-тиолов
ORCID ID: 0000-0001-7401-9458
Keywords: 5-(thiophene-3-ylmethyl)-4-R-1,2,4-triazole-3-thiol; synthesis; physical and chemical properties; 5-(тіофен-3-ілметил)-4-R-1,2,4-тріазол-3-тіол; синтез; фізико-хімічні властивості; 5-(тиофен-3-илметил)-4-R-1,2,4-триазол-3-тиол; физико-химические свойства